grammatical evidence between unknown poetry and Quranic readings - (Al-Mufassal) by Al-Zamakhshari as a model - (Journal of the College of Basic Education, 2023)
Poetic, of which more than ninety witnesses are not known to say, and more than eighty witnesses are different in their attribution to saying their own eyes, so we have - as Dr. Fadel said - more than seventy and one hundred witnesses of which the real saying is not known (1).